The Role Of Electronic Health Records In Improving Patient Care (The Review of Diabetic Studies, 2024)
Background: Electronic health records (EHRs) have revolutionized modern healthcare by replacing traditional paper-based systems with integrated digital platforms designed to enhance the accuracy, efficiency, and safety of patient care. Understanding healthcare professionals’ experiences and perceptions regarding EHR utilization is essential for evaluating their role in improving clinical outcomes and identifying areas for system enhancement.Methods: A descriptive cross-sectional study was conducted among 210 healthcare professionals, including physicians, nurses, and allied health staff. Participants were selected through stratified random sampling. Data were collected using a validated self-administered questionnaire that assessed demographics, EHR utilization patterns, perceived impacts on patient care, and challenges encountered. Data were analyzed using SPSS version 26, applying descriptive statistics and inferential analysis (Chi-square and ANOVA tests) with a significance level of p < 0.05.Results: The majority of participants (78.6%) reported daily use of EHRs, and 81.9% had received formal EHR training. Most respondents agreed that EHRs improved accuracy of patient data (90.4%), enhanced communication among providers (88.1%), and reduced medical errors (86.7%). Efficiency and time management were positively influenced in 88.1% of cases. However, challenges were identified, including lack of interoperability (81.9%), system downtime (80.9%), and data security concerns (78.5%). A statistically significant difference was found in perceptions of EHR effectiveness among professional groups (p = 0.031), with physicians showing the highest satisfaction.Conclusion: EHRs were perceived as essential tools for improving patient care through enhanced accuracy, coordination, and safety. Despite notable challenges related to system performance and data privacy, the overall findings highlight the positive impact of EHRs on healthcare delivery. Continuous training, stronger interoperability, and improved technical support are recommended to optimize system efficiency and further advance patient-centered care.